Phosphorus limitation relates to diet selection of sheep and goats on dry calcareous grassland. Issue 1 (24th August 2015) - Hejcmanová, Pavla; Pokorná, Pavlína; Hejcman, Michal; Pavlů, Vilém
Abstract: Aims: We aimed to (1) identify the nutritive value of late season herbage of principal species on dry calcareous grassland, (2) study the forage supply for sheep and goats and the degree of its exploitation by these animals, (3) identify the animals' preference for particular plant species and types (grass, forb, shrub), and (4) identify the indicators of diet selection at the scale of the functional traits and nutritional value of selected plant species. Location: Pálava Protected Landscape Area, Czech Republic (48°50′ N, 16°38′ E). Methods: The investigation was based on the rotational grazing of sheep and goats for conservation purposes from Aug to Sept 2008. In all paddocks, the plant species composition and cover were identified. Animals were observed for 14 h a day to record their diet. Diet selectivity regarding 17 plant species and type was calculated. For ten plant species, the functional traits, i.e. canopy height, specific leaf area (SLA), leaf dry matter content (LDMC) and nutritive value, were measured. Differences in diet selection by sheep and goats and the drivers of diet selection were assessed. Results: Of a total of 138 plant species recorded in all paddocks, sheep and goats grazed on 136 and 126, respectively. Sheep grazed more selectively on forbs than on grasses and shrubs, whereas goats grazed on forbs preferentially, on shrubs in conformity with supply in the vegetation cover, and avoided grasses. The diet selectivity of both sheep and goats was similar and was positively correlated with a high concentration of N, P, K, Ca and Mg, which were particularly high in the leaves of Prunus spinosa and lowest in Bromus erectus, and negatively correlated with the LDMC and fibre content in grasses. Conclusions: Dry nutrient‐poor calcareous grassland in the late season did not offer animals more macronutrients than required for their maintenance. The animals adapted their foraging strategy to select preferentially forbs or woody species particularly rich in P and with a relatively low fibre content, the real indicators of diet selection. Late grazing could therefore contribute to the control of woody plant species, but cannot suppress expansive grasses. Abstract : Sheep and goats select a wide range of plant species on dry calcareous grassland. In the late season did not offer animals more macronutrients than required for their maintenance. The animals adapted their foraging strategy to select preferentially forbs or woody species particularly rich in P and with a relatively low fibre content. Late grazing could therefore contribute to the control of woody plant species, but cannot suppress expansive grasses.